2020
DOI: 10.1111/1348-0421.12794
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mTOR inhibitors during CMV disease in kidney transplant recipients: Results of a pilot retrospective study

Abstract: AbstractmTOR inhibitors exert a preventive effect on cytomegalovirus (CMV) disease in CMV seropositive (R+) kidney transplant recipients, but their impact during the curative treatment of CMV disease in high‐risk kidney transplant recipients has not been investigated. We aimed to evaluate the efficacy and tolerance of mTOR inhibitors compared with mycophenolic acid in 63 consecutive kidney transplant recipients (80% of D+R−) suffering from CMV disease with a persistent or a recurrent CMV DNAemia. In this monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This case report shows that high-dose CMV-IVIG may represent a valuable alternative in patients with multidrug-resistant strains, which has shown efficacy as adjunct therapy of CMV infections ( 10 ). In addition, although mTOR inhibitors may be more effective in CMV prevention than control ( 11 , 12 ), early conversion of immunosuppressive drugs to a regimen containing an mTOR inhibitor may have at least in part contributed to viral control in our patient ( 11 , 13 ). This may be related to its direct antiviral activity ( 4 ).…”
Section: Discussionmentioning
confidence: 92%
“…This case report shows that high-dose CMV-IVIG may represent a valuable alternative in patients with multidrug-resistant strains, which has shown efficacy as adjunct therapy of CMV infections ( 10 ). In addition, although mTOR inhibitors may be more effective in CMV prevention than control ( 11 , 12 ), early conversion of immunosuppressive drugs to a regimen containing an mTOR inhibitor may have at least in part contributed to viral control in our patient ( 11 , 13 ). This may be related to its direct antiviral activity ( 4 ).…”
Section: Discussionmentioning
confidence: 92%
“…But another study showed that switching to mTORI seemed inadequate for improving CMV clearance or preventing CMV recurrences. 4 When converting from mycophenolate mofetil (MMF) to EVR, a trend was demonstrated toward improved viral clearance, but did not reach statistical significance, in BKPyV infection. 5 A trial evaluating switching RTxRs from TAC/MMF to either EVR with reduced calcineurin inhibitor (CNI) or MMF with reduced CNI to treat BK polyomavirus infection resulted in no difference between the combination therapy and MMF with reduced CNI in the combined end point of resolution of BK viremia or 50% reduction in viruria.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the incidence of CMV and BKPyV infections was lower in the EVR group compared with the MPA group (CMV: 3.6% versus 13.3%, p < 0.001; BKPyV: 4.3% versus 8.0%, p < 0.001, respectively). But another study showed that switching to mTORI seemed inadequate for improving CMV clearance or preventing CMV recurrences 4 . When converting from mycophenolate mofetil (MMF) to EVR, a trend was demonstrated toward improved viral clearance, but did not reach statistical significance, in BKPyV infection 5 .…”
Section: Introductionmentioning
confidence: 99%